Vibrational properties of 1D- and 3D polynuclear spin crossover Fe(II) urea-triazoles polymer chains and quantification of intrachain cooperativity. (22nd October 2020) - Wolny, Juliusz A; Hochdörffer, Tim; Sadashivaiah, Sakshath; Auerbach, Hendrik; Jenni, Kevin; Scherthan, Lena; Li, Ai-Min; von Malotki, Christian; Wille, Hans-Christian; Rentschler, Eva; Schünemann, Volker
Abstract: The vibrational dynamics of the iron centres in 1D and 3D spin crossover Fe(II) 4-alkyl-urea triazole chains have been investigated by synchrotron based nuclear inelastic scattering. For the 1D system, the partial density of phonon states has been modelled with density functional theory methods. Furthermore, spin dependent iron ligand distances and vibrational modes were obtained. The previously introduced intramolecular cooperativity parameter H coop (Rackwitz et al, Phys. Chem. Chem. Phys. 2013, 15, 15450) has been determined to −31 kJ mol −1 for [Fe( n -Prtrzu)3 (tosylate)2 ] and to +27 kJ mol −1 for [Fe( n -Prtrzu)3 (BF4 )2 ]. The change of sign in H coop is in line with the incomplete and gradual character of the spin transition for the former as well as with the sharp transition for the latter reported previously (Rentschler and von Malotki, Inorg. Chem., Act. 2008, 361, 3646). This effect can be ascribed to the networks of intramolecular interactions in the second coordination sphere of the polymer chains, depending on the spin state of the iron centres. In addition, we observe a decreased coupling and coherence when comparing the system which displays a sharp spin transition to the system with an incomplete soft transition by analyzing molecular modes involving a movement of the iron centres.